2010
DOI: 10.1111/j.1460-9568.2010.07291.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the parietal lobe syndrome from a neurophysiological and evolutionary perspective

Abstract: In human and nonhuman primates parietal cortex is formed by a multiplicity of areas. For those of the superior parietal lobule (SPL) there exists a certain homology between man and macaques. As a consequence, optic ataxia, a disturbed visual control of hand reaching, has similar features in man and monkeys. Establishing such correspondence has proven difficult for the areas of the inferior parietal lobule (IPL). This difficulty depends on many factors. First, no physiological information is available in man on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 210 publications
3
59
0
4
Order By: Relevance
“…Previous studies have demonstrated a caudo-rostral gradient in PPC responses when comparing movement planning for saccades and hand movements in monkeys (Burnod et al, 1999;Caminiti et al, 2010) and humans (Astafiev et al, 2003;Connolly et al, 2003;Medendorp et al, 2005;Beurze et al, 2007Beurze et al, , 2009Connolly et al, 2007;Filimon et al, 2009). The current study confirms those findings, but also indicates that they cannot be interpreted as evidence for effector-specific, somatotopic organization of PPC (Chang et al, 2008;Andersen and Cui, 2009).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Previous studies have demonstrated a caudo-rostral gradient in PPC responses when comparing movement planning for saccades and hand movements in monkeys (Burnod et al, 1999;Caminiti et al, 2010) and humans (Astafiev et al, 2003;Connolly et al, 2003;Medendorp et al, 2005;Beurze et al, 2007Beurze et al, , 2009Connolly et al, 2007;Filimon et al, 2009). The current study confirms those findings, but also indicates that they cannot be interpreted as evidence for effector-specific, somatotopic organization of PPC (Chang et al, 2008;Andersen and Cui, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…To conclude, we report that PPC is organized according to a caudo-rostral visual-to-somatic gradient in PPC (Burnod et al, 1999;Beurze et al, 2007Beurze et al, , 2009Levy et al, 2007;Caminiti et al, 2010). Contrary to common view, this gradient does not seem to reflect effector specificity beyond a crude distinction between eye movements and movements of other body parts.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…This condition can be caused by either the failure to effectively analyze the spatial structure of a model (perceptual function) or coordinate motor output to reproduce the structure through a sequence of actions (motor function) (2). Whether the former or latter is related to the failure in reproducing visual figures is usually unclear in each patient in clinical practice; therefore, the more general term "constructional disability" is also used to describe this condition.…”
Section: Introductionmentioning
confidence: 99%